Assessment of indicators of range of motion and strength of individual muscle groups in children with consequences of hip dysplasia - Anna Rudenko; Yurij Liannoi; Oleksandr Zviriaka (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the features of functional disorders of the hip joints, formed as a result of dysplasia in preschool children. Material and methods: 131 children of preschool age (average age 5,6 ± 0,5 years) participated in the research, which was conducted during 2014-2019. Participants were divided into two main groups: the main group (MG, n = 68) - children with a history of developmental hip dysplasia (DDH) (identified by the analysis of medical records) and a comparison group (CG, n = 63) - children without hip joint disorders. To evaluate the results, we used the method of strain dynamometry (manual muscle tester with a mechanical force sensor «EXPANDER") and the method of goniometry. Research results: the research results of electrotensodynamic measurements of lower extremities muscles in children of MG indicate a significant decrease in the strength of the muscles-abductors of the thigh (m. gluteus medius, m. gluteus minimus, m. tensor fasciae latae) of the injured limb relatively intact (intact - 85,8 ± 6,8 and affected 54,5 ± 4,9 (( ± S), (p ≤ 0,05)) and hypertonicity of the thigh- adductor muscles (m. gracilis, m. adductor longus, m. adductor brevis) from the affected limb relative to the intact limb (intact - 68,2 ± 4,4, affected - 95,8 ± 4,1, ( ± S), (p ≤ 0,05). The research of the indicators of tensodynamometry of children with DDH revealed a strong direct correlation between the state of the muscular system and the development of the adduction contracture of the hip joint (correlation coefficient between the strength indicators of the muscles-abductors of the thigh and the amplitude of abduction (r = 0,7 (strong straight ligament, p <0,05)). Conclusions: tensodynamometric examination of the muscles revealed a decrease in the tone of the abductor muscles of the thigh, biceps femoris, m. semitendinosus, m. semimembranosus, m. quadriceps femoris, m. sartorius. The result of the functional activity of the muscles is the formation of a torsion-valgus deformity of the hip joint, which requires a step-by-step individual implementation of rehabilitation and corrective interventions.